Utility of Stability and Tear Location in a Classification System for Discoid Meniscus Surgical Planning. Issue 1 (January 2022) - Yang, Brian; Logan, Catherine A.; Feroe, Aliya G.; Kocher, Sophia D.; Williams, Kathryn A.; Kocher, Mininder S.
Abstract : Background: Despite the presence of multiple classification systems for discoid meniscus, no system has yet to demonstrate utility in predicting the need for meniscal repair. The purpose of this study was to correlate characteristics associated with meniscal repair and propose a model that can inform preoperative planning and initial counseling of surgical plans and expectations. Methods: Medical and operative records of 434 knees with lateral discoid meniscus in children and adolescents treated between 1991 and 2016 were reviewed retrospectively to determine the surgical procedure performed (saucerization with or without meniscal repair), discoid meniscal morphology and stability, and location and type of any associated tear. Univariate associations between discoid meniscal characteristics and surgery type were calculated and a logistic regression model of surgery type was generated. Results: In univariate models, unstable menisci (93%, or 179/204, P <0.001) and menisci with tears extending peripherally (75%, or 85/204, P <0.001) were more likely to receive surgery with repair. In isolation, instability demonstrated 89% sensitivity and 94% specificity in predicting surgery with repair. A logistic regression model including stability, tear, and their interaction (stability×tear) showed that that the odds of unstable lateral discoid menisci receiving surgery with repair was 114 times higher than stable menisci ( P <0.001) while lateral discoid menisci with peripherally extending tears had 6.4 times higher odds of receiving repair than those that had an isolated central tear ( P <0.001). Conclusion: Stability and tear location of lateral discoid menisci were associated with surgical treatment in univariate and logistic regression models. The proposed classification system, in which menisci are classified by stability [Stable (S0), Unstable (S1), morphology (Incomplete (M0), Complete (M1))], and tear [No tear (T0), Central tear, isolated (T1), or Central tear, peripheral extension (T2)], is easily remembered and predicts surgical repair for discoid menisci. This scheme can serve to inform preoperative planning and initial counseling of primary surgical management and postoperative expectations. Subsequent research should develop a system that predicts meniscal survival and patient outcomes following the index operation. Level of Evidence: Level III.